Rancang Bangun Aplikasi Pendeteksi Penyakit Ginjal Kronis dengan Menggunakan Algoritma C4.5 - Robi Rianto; Ni Made Satvika Iswari (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2017)
Kidneys are two bean-shaped organs, each about the size of a fist. They are located just below the rib cage, one on each side of the spine. Kidneys are vital organs contained in the human body and serve to filter the blood of metabolic waste product and throw it in the form of urine. Given the changing conditions in the body can affect the kidneys, causing a decrease in the function of these organ and lead to chronic kidney disease. In an article on the website of the National Institute of Diabetes and Digestive and Kidney Diseases (2014) argued that chronic kidney disease is a silent disease, in which patients appear normal and show no symptomp but the test results stating the patient’s kidney function had decreased. Based on the above information, the research on how to detect chronic kidney disease will be conducted. Applications built on the basis of desktop and using Decision Tree algorithm C4.5. The trial was conducted to determine how much the level of accuracy that can be generated by the application. The testing process is done by using cross-validation and based on the results already calculated this application has an accuracy of 91.50% at the time of the decision tree is made without using preprocess menu. Index Terms— C4.5, chronic kidney disease, decision tree, detection system.